Training-specific muscle architecture adaptation after 5-wk training in athletes - Blazevich, A. J.; Gill, N. D.; Bronks, R.; Newton, R. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: This study examined changes in the muscle size, muscle architecture, strength, and sprint/jump performances of concurrently training athletes during 5 wk of "altered" resistance training (RT). METHODS: Eight female and 15 male athletes performed 4 wk of sprint, jump, and resistance training in addition to their sports training (standardization) before adopting one of three different programs for 5 wk: 1) squat lift training (SQ, N = 8) with sprint/jump training; 2) forward hack squat training (FHS, N = 7) with sprint/jump training; or 3) sprint/jump training only (SJ, N = 8). Muscle size, fascicle angle, and fascicle length of the vastus lateralis (VL) and rectus femoris (RF) muscles (using ultrasound procedures) as well as 20-m sprint run, vertical jump, and strength performance changes were examined. RESULTS: A small increase in VL fascicle angle in SQ and FHS was statistically different to the decrease in SJ subjects (P < 0.05 at distal, P < 0.1 at proximal). VL fascicle length increased for SJ only (P < 0.05 at distal, P < 0.1 at proximal) and increased in RF in SQ subjects (P < 0.05). Muscle thickness of VL and RF increased in all training groups (P < 0.05) but only at proximal sites. There were no between-group differences in squat, forward hack squat, or isokinetic strength performances, or in sprint or jump performances, despite improvements in some of the tests across the groups. CONCLUSIONS: Significant muscle size and architectural adaptations can occur in concurrently training athletes in response to a 5-wk training program. These adaptations were possibly associated with the force and velocity characteristics of the training exercises but not the movement patterns. Factors other than, or in addition to, muscle architecture must mediate changes in strength, sprint, and jump performance.